2008
DOI: 10.1084/jem.20080767
|View full text |Cite
|
Sign up to set email alerts
|

Lipid mediators in innate immunity against tuberculosis: opposing roles of PGE2 and LXA4 in the induction of macrophage death

Abstract: Virulent Mycobacterium tuberculosis (Mtb) induces a maladaptive cytolytic death modality, necrosis, which is advantageous for the pathogen. We report that necrosis of macrophages infected with the virulent Mtb strains H37Rv and Erdmann depends on predominant LXA4 production that is part of the antiinflammatory and inflammation-resolving action induced by Mtb. Infection of macrophages with the avirulent H37Ra triggers production of high levels of the prostanoid PGE2, which promotes protection against mitochondr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

18
372
2
11

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 319 publications
(403 citation statements)
references
References 66 publications
18
372
2
11
Order By: Relevance
“…Furthermore, inhibition of the infection-induced switch to glycolysis results in decreased PTGS2, in parallel with decreased IL-1b production. Interestingly, Chen et al (20) reported reduced PTGS2 induction in response to virulent H37Rv compared with avirulent H37Ra, which, combined with our observations, may im- plicate reduced efficacy of the downstream sequelae of glycolytic reprogramming in increased susceptibility to the virulent strain.…”
Section: Discussionsupporting
confidence: 78%
“…Furthermore, inhibition of the infection-induced switch to glycolysis results in decreased PTGS2, in parallel with decreased IL-1b production. Interestingly, Chen et al (20) reported reduced PTGS2 induction in response to virulent H37Rv compared with avirulent H37Ra, which, combined with our observations, may im- plicate reduced efficacy of the downstream sequelae of glycolytic reprogramming in increased susceptibility to the virulent strain.…”
Section: Discussionsupporting
confidence: 78%
“…suspect that Rv1050 may affect fatty acid metabolism in the macrophage. It is known that M. tuberculosis-infected macrophages exhibit an altered arachidonic acid metabolism in favor of lipoxin A 4 over prostaglandin E 2 (PGE 2 ), which promotes necrosis over apoptosis (52,55). Although it is unknown how M. tuberculosis affects this process, it is reasonable to conjecture that exported proteins are used to manipulate the metabolism of the macrophage.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in addition to the antiapoptotic effects of LXA 4 , it has been described that this LX prevents PGE 2 synthesis and this strategy is used by virulent Mycobacterium tuberculosis strains to avoid repair of the macrophage plasma membrane and to promote necrosis at the time the pathogen evades macrophage function. 8 Therefore, although their role as antiinflammatory compounds is well documented, their implication in apoptosis has been a matter of debate. 1,3,5,26 Opposite actions of LXs on the balance between survival and apoptosis have been reported in neutrophils when signaling through the pleiotropic formylpeptide receptor like-1/LXA 4 receptor.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 In mammals, lipoxygenase enzymes (LOXs) generate two main native products: lipoxin A 4 (LXA 4 ) and B 4 (LXB 4 ), with LXA 4 being the most studied, which exerts potent anti-inflammatory actions modulating leukocyte trafficking and promoting phagocytic clearance of apoptotic cells. 7,8 The effects of LXs as lipid mediators with potent anti-inflammatory actions are well documented, but their role in apoptosis remains controversial. 9 For instance, an apoptotic effect on fibroblasts after treatment with LXA 4 at micromolar concentrations has been described, 10 whereas it has been also reported that this compound inhibits peroxynitrite formation in leukocytes, 11 reduces colonocyte apoptosis 12 and promotes survival of retinal pigment epithelial cells.…”
mentioning
confidence: 99%